Implementasi Transformational Leadership Dan Meaning In Work Terhadap Employee Performance Karyawan - Febryantahanuji Febryantahanuji; Haryo Kusumo (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Leadership style is one of the factors of employee performance so that a good leadership style will be able to direct and give instructions to the work faced by employees. A good leadership style will also lead to job satisfaction for them, so they will work with feelings of pleasure and joy. Simultaneously, the Transformational Leadership Variable has a significant effect on Employee Performance with a value of Fcount > from Ftable. The result of the Coefficient of Determination (Adjusted R Square) is 0.165, meaning that the Employee Performance variable can be explained by the Transformational Leadership variable and the Meaning in Work variable by 16.5% while the remaining 83.5% is influenced by other variables.